NEED for review of monetary and fiscal policies. (1995)
At the root of the current chaotic conditions in the financial system in general and the money market in particular are the unplanned borrowings by the government to finance its revenue deficit. The size of domestic saving is simply not enough to finance such large borrowings without starving productive sectors of institutional credit. What is called for is nothing less than a total reappraisal of monetary and field policies
Keywords: Devaluation of currency - India; India - Economic policy; Monetary policy - India